SALMONELLOSIS - SYMPTOMS, TREATMENT (Proceedings of International Educators Conference, 2024)
Salmonellosis is an acute infectious disease caused by bacteria belonging to the genus Salmonella, transmitted by the fecal-oral mechanism, and mainly caused by damage to the gastrointestinal tract.